The Perspective of the Malay Community in the Livelihood of Street Angklung Musicians in Malioboro Yogyakarta - Fransisca, Malia; Panorama, Maya (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The purpose of this study is to see how the views of the Malay community in the livelihoods of angklung musicians who are played in Yogyakarta by using the theory of structural functionalism. Angklung music performances in Yogyakarta are multifunctional. This means that now angklung music does not only present angklung as a traditional musical instrument, but also as a profession. Such as the transformation of the song being performed and the addition of dancers to attract the audience’s attention. The method used in this research is descriptive qualitative with a library research approach. Data collection techniques in this study ar observation, interviews and documentation. The sample in this study in the Malay community who have lived in Yogyakarta, both for study and work. Form the observations and interviews that have been conducted, it shows that there are two views, namely positive and negative. This positive view is obtained because it is considered that the angklung musician profession is a form of high level creativity of the nation’s childern which not everyone can do it. With traditional instruments, but the arrangement and presentation of different music provides a special attraction for the audience. Then the negative view emerged because the movements of the dancers accompanying the angklung music were classified as erotic and contained element of sensuality toward the audience.